SUSTAINABLE DEVELOPMENT GOALS: ANALYSIS FACTORS NO POVERTY IN JAVA - Jetlikhsan, Daud; Boedirochminarni, Arfida (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
The Sustainable Development Goals are in line with Indonesia's vision and mission. One of the 17 SDGs, is zero poverty. Poverty gets the most attention because all the SDGs are some kind of effort to achieve the goal of "no poverty". With the help of this research, it is helpful that the realization of the success factors of the sustainable development goals without poverty can be known as the critical success factors. Data on the unemployment rate, Human Development Index, inflation, and poverty are collected from the Central Bureau of Statistics. The official website was used to collect data covering six provinces in Java Island for ten years. Panel data regression analysis is the analysis method used in this study. In every province in Java, one of the most influential factors in reducing poverty is the Human Development Index or the quality of each individual.